POLYMORPHISMS IN BMPR1B AND INHβA GENES ARE ASSOCIATED WITH LITTER SIZE IN INDIGENOUS SHEEP OF BANGLADESH - R. Basrin; R. Khanom; M. M. Hossain; M. S. Islam; A. K. F. H. Bhuiyan; M. S. A. Bhuiyan (Journal of Animal and Plant Sciences, 2023)
The purpose of the study was to detect the genetic polymorphisms in the fragments of four transforming growth factors β superfamily genes (BMPR1B, INHβA, BMP15 and GDF9) and to investigate their possible association with litter size trait in Bangladeshi indigenous sheep population. Previously reported six significantly associated single nucleotide polymorphisms (SNPs) of those aforementioned genes were included in this study. A panel of 12 samples were sequenced from each gene fragment for polymorphism detection. Multiple sequence alignment revealed polymorphic sites only for BMPR1B (c.746A>G) and INHβA (c.218A>G) gene fragments in indigenous sheep of Bangladesh. However, four other polymorphisms located in GDF9 [c.260G>A (FecG1) and c.1184C>T (FecG8)] and BMP15 [c.69C>T (FecX-H and c.718C>T (FecX-G)] gene fragments were absent in the studied populations. PCR-RFLP and resequencing were employed for genotyping of BMPR1B and INHβA polymorphisms, respectively. The mean litter size of ++, +B and BB genotypes of BMPR1B gene were 1.19±0.07, 1.44±0.09 and 2.13±0.09, respectively. Besides, the average litter size of AA, AG and GG genotypes of INHβA gene mutation was 2.11±0.39, 1.70±0.30 and 2.83±0.40, respectively. Litter size had significant association with BMPR1B (p<0.05) and INHβA (p<0.01) genotypes and regional population specific and therefore, could be used as molecular markers for improving prolificacy of Bangladeshi indigenous sheep.
Keywords: Single nucleotide polymorphism; allele; genotype; sheep; prolificacy; Bangladesh